Entre a proteção e a vulnerabilidade: significados atribuídos ao uso de drogas entre adolescentes de escola pública de período integral - Pires, Laurena Moreira (2018)
Objectives: To identify and to analyze aspects related to the relational and labor insertion of adolescents attending a full-time school; and to investigate the relationship between adolescents' social vulnerability and the abusive and harmful use of psychoactive drugs. Methodology: This is a social research, with a qualitative approach of a strategic type, developed from January 2016 to December 2017. For data collection, we used the technique of focus groups guided by a predetermined script. A total of 49 adolescents aged 15 to 19 years attending a Full-time Education Center (CEPI), located in the eastern region of Goiânia- Goiás, participated in the study. Focus groups were held in the school environment. Results and discussion: The content analysis of the participants' speeches allowed the construction of four categories of analysis: "Tell us where it came from"; "With whom you walk"; "If you study, how to work?"; "Drugs: non-parallel universe". The family, the school and the group of friends were pointed out as the main groups for the relational insertion of these subjects. The adolescents presented themselves influenced by the context of economic fragility to which their families were exposed, which, in turn, motivated that they were inserted in groups of equals in that context. The meanings attributed to the world of work involved the search for family emancipation and the acquisition of consumer items. The duality faced by the adolescents resided in the impossibility of attending to the immediate desire to enter the labor market given the insertion in a full-time school, becoming an important conflict for these subjects. On the other hand, psychoactive drugs were widely present in the social context of these adolescents, permeating the meanings attributed to their relational insertions. In this sense, even if they did not use them, they felt their effects, even capable of leading them to disaffiliation. Final considerations: Finally, it was concluded that the social vulnerability of the group of participating adolescents, and of many other Brazilians, is related to the effects of poor income distribution, and this is expressed in families because of precariousness and insecurity. insertion in work, fragility of social relations permeated and subsidized by the harmful use of psychoactive substances, as well as inefficiency of social protection institutions and the State, in this case, full-time public school.